Peran Supervisi Pendidikan Dalam Meningkatkan Kualitas Pendidikan Di Era Digital - Arnita Niroha Halawa; Dety Mulyanti (Pendekar : Jurnal Pendidikan Berkarakter, 2024)
Educational supervision at the elementary school level is an activity that aims to improve the quality of learning in that environment. Considering technological developments in the digital era, educational supervision also needs to adapt to existing technological advances. In its implementation, this supervision involves a number of processes that focus on problem solving in order to increase teacher efficiency and effectiveness. Apart from that, his role also involves improving the quality of learning in Indonesia, which is currently still far from the expected standards. The supervisory role includes responsibility for improving the quality of teacher teaching by following advances in science and technology, as well as implementing supervision techniques. Based on data analysis, educational supervision is proven to have a significant role in improving the quality of teaching. This article uses a literature study method and will discuss the definition of educational supervision, the role of supervision in improving the quality of learning, challenges in implementing supervision in the digital era, and strategies for overcoming these challenges.